2018
DOI: 10.22153/kej.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of an Automatic Control for Two Axis Tracking System for Applications of Concentrated Solar Thermal Power

Abstract: The present work presents design and implementation of an automated two-axis solar tracking system using local materials with minimum cost, light weight and reliable structure. The tracking system consists of two parts, mechanical units (fixed and moving parts) and control units (four LDR sensors and Arduino UNO microcontroller to control two DC servomotors). The tracking system was fitted and assembled together with a parabolic trough solar concentrator (PTSC) system to move it according to information come f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…AC motor of 1600 rpm was used to rotate the centrifugal container, in addition to measure the humidity inside the crystallization unit the humiditytemperature sensor (DHT11), were used. On the other hand the system also includes electronic parts: three uno-arduinos [12], each of them is responsible for one of the sensors and to convert Analog-to-digital signal (ADC). Six relays as a latching relays, that were used to convert the DC arduinos output signals into appropriate signals to enter the PLC as an input.…”
Section: Mechanicaland Electronic Partsmentioning
confidence: 99%
“…AC motor of 1600 rpm was used to rotate the centrifugal container, in addition to measure the humidity inside the crystallization unit the humiditytemperature sensor (DHT11), were used. On the other hand the system also includes electronic parts: three uno-arduinos [12], each of them is responsible for one of the sensors and to convert Analog-to-digital signal (ADC). Six relays as a latching relays, that were used to convert the DC arduinos output signals into appropriate signals to enter the PLC as an input.…”
Section: Mechanicaland Electronic Partsmentioning
confidence: 99%
“…Solar thermal technology faces many engineering obstacles, researchers have proposed many technologies to improve the solar thermal efficiency of parabolic dish concentrators using different tracking technologies. (Tami et al, 2018) has proposed a two-axis tracking system to increase the efficiency of parabolic trough solar concentrators to heat water up to 89C° and showed that the dual axis tracking efficiency was increased by 23% in comparison to the fixed system. (Mahmood and Al-Salih, 2018) has compared two solar dish concentrators, the first was covered with small pieces of mirror and the other one was covered with miller paper, results showed that the mirror-covered dish efficiency is improved due to having a better reflecting surface.…”
Section: Introductionmentioning
confidence: 99%
“…As known, electricity production stations work either by fuel, gas or other resources, so the use of these resources profusely leads to an increase in the percentage of pollution. Thus, the use of renewable energy becomes a crucial need to be applied to reduce the percentage of pollution as well as reduce the excessive use of natural resources for electricity production [2][3][4][5]. Countries began to find a reliable and applicable source of renewable energy.…”
Section: Introductionmentioning
confidence: 99%